Characterization of the dynamics of novel conjugated bile acids in relation to the development of islet cell autoantibodies - Karmacharya, Pragya (My University, 2023)
Bile acids (BAs) are formed in the liver and modified by gut microbes (GMs) as secondary BAs. Alteration of secondary BAs has been found in children preceding the appearance of islet cell autoantibodies (ICAs) and type 1 diabetes (T1D). Not much is known about newly discovered microbially conjugated BAs named as bile acid amidates (BAAs). In mass spectrometry, Data-dependent acquisition (DDA) and Sequential window acquisition of all theoretical mass spectra (SWATH) are the two untargeted data acquisition modes having their own strategy to collect precursor ions for fragmentation affecting metabolites identification. We developed and optimized the method in DDA and SWATH to identify 110 BAAs and compared their coverage. Then, with the optimal and better acquisition mode, we study the dynamics of BAAs in fecal samples (n=303) from a subset (n=74) of DIABIMMUNE study children in a longitudinal series with three cases: children who develop single ICAs (PA1Ab), multiple ICAs (PA2Ab) or who remained ICAs negative during follow-up. This study shows that DDA outperforms SWATH with better coverage of BAAs. Here, we identified 78 out of 110 BAAs. Further analysis revealed age as a cofounding factor of BBAs. Moreover, we observed an increasing trend in BAAs associated with secondary BAs as age decreases. The significant alteration was mainly observed at 18 months of age in PA2Ab as compared to PA1Ab. This finding can contribute to a better understanding of the pathogenesis of T1D for early detection and prevention.
Keywords: BAs, BAAs, ICAs, T1D, PA1Ab, PA2Ab, DDA, SWATH